Current HLA Investigations on SARS-CoV-2 and Perspectives - Douillard, Venceslas; Castelli, Erick C.; Mack, Steven J.; Hollenbach, Jill A.; Gourraud, Pierre-Antoine; Vince, Nicolas; Limou, Sophie; , for the Covid-19|HLA & Immunogenetics Consortium and the SNP-HLA Reference Consortium (Frontiers in Genetics, 2021)
The rapid, global spread of the SARS-CoV-2 virus during the current pandemic has triggered numerous efforts in clinical and research settings to better understand the host genetics’ interactions and the severity of COVID-19. Due to the established major role played by MHC/HLA polymorphism in infectious disease course and susceptibility, immunologists and geneticists have teamed up to investigate its contribution to the SARS-CoV-2 infection and COVID-19 progression. A major goal of the Covid-19|HLA & Immunogenetics Consortium is to support and unify these efforts. Here, we present a review of HLA immunogenomics studies in the SARS-CoV-2 pandemic and reflect on the role of various HLA data, their limitation and future perspectives.